Implementation of TQM Education in Increasing Interest in Learning Tetum as the National Language of Timor Leste - Alexandra de Araujo Tilman; Marinu Waruwu; Bambang Ismanto (Ridwan Institute, 2023)
This research aims to evaluate the implementation of Total Quality Management (TQM) in schools, specifically focusing on Tetum language learning at Damea Liquitei Maubisse Elementary School. The study used a descriptive qualitative method to conduct field research involving the development team, teachers, and principals as key informants. The research sheds light on the concerted efforts to implement TQM in educational settings and its implications. Key areas of investigation include TQM goals in schools, challenges encountered in TQM application, and the tools utilized to develop Tetum language learning within the TQM framework. The findings contribute valuable insights to the broader discourse on enhancing educational quality through TQM practices.